Seed dispersal and tree legacies influence spatial patterns of plant invasion dynamics - Lu, Yuanming; Xia, Junfei; Magee, Lukas J.; DeAngelis, Donald L. (Frontiers in Applied Mathematics and Statistics, 2023)
Invasive plant species alter community dynamics and ecosystem properties, potentially leading to regime shifts. Here the invasion of a non-native tree species into a stand of native tree species is simulated using an agent-based model. The model describes an invasive tree with fast growth and high seed production that produces litter with a suppressive effect on native seedlings, based loosely on Melaleuca quinquenervia, invasive to southern Florida. The effect of a biocontrol agent, which reduces the invasive tree’s growth and reproductive rates, is included to study how effective biocontrol is in facilitating recovery of native trees. Even under biocontrol, the invader has some advantages over native tree species; ability to tolerate higher stem densities than the invaded species and its litter’s seedling suppression effect. We also include a standing dead component of both species, where light interception from dead canopy trees influences neighboring tree demographics.